KOMPONEN KETERAMPILAN METAKOGNISI SISWA DALAM PEMECAHAN MASALAH MATEMATIKA DI SMA AL-AZHAR MANDIRI PALU - Sudarman Bennu; Multazam Multazam (Absis: Mathematics Education Journal, 2021)
This research aims to identified and obtain a description metacognition skill components of students in SMA Al-Azhar Mandiri Palu to solving mathematical problem about linear program based on the level of mathematical ability of the students. The type of this research is qualitative research. The subject of this research is the students of class XII D SMA-Al-Azhar Mandiri Palu who have high, medium and low math ability. Data were collected by video recording, test method and interview. The results of this study indicate that subjects with high math ability, namely NF has a complete metacognition skill components that is prediction, planning, monitoring, and evaluation with regular and repetitive patterns. Subjects with medium math ability, namely HN also has a complete metacognition skill components that is prediction, planning, monitoring, and evaluation but the patterns is irregular and repetitive. And the subject of low math ability, namely TS has only three metacognition skill components that is prediction, planning, and evaluation with non-repetitive patterns.